The role of financial incentives – as SMB development factor (Journal of Economic Research & Business Administration, 2017)
The paper considers the role of financial incentives for the development of entrepreneurship. Itrevealed the contribution of small and medium-sized businesses in the country’s economy. Accordingto state programs in Kazakhstan, such as the Strategic Plan of Development of Kazakhstan till 2050,the State program for accelerated industrial-innovative development of Kazakhstan for 2015-2019, thedevelopment of small and medium-sized businesses identified as a priority. The experience of foreigncountries such as the US, Japan and France, financial incentives for small and medium-sized businesseswere Reviewed and analyzed. The negative factors for the development of small and medium businessin Kazakhstan were identified . the state financial measures to stimulate entrepreneurship was presented,the most common form used by tax incentives, forms of state financial and credit support of small businesswere described, measures to improve the financial - banking system were proposed contributing tothe development of small medium-sized businesses.